Estilos de desarrollo, deforestacion y degradacion de los bosques en las tierras bajas de Bolivia - Balanza, P.P. (CIFOR, Centro de Estudios para el Desarrollo Laboral y Agrario, Teller de Iniciativas en Estudios Rurales y Reforma Agraria, 1998)
This book looks at the history of lowland forest in Bolivia from the beginning of the century to the present time. It allows us to understand why the rate of deforestation in Bolivia has increased so dramatically and the minor use of just forestry or environmental base actions compared to the influence of other actors. The causes of deforestation and forest degradation are not in the forest but have their origins in policies, macro-economic, international and domestic markets, migrations and social changes. This research is included in a CIFOR initiative to study the relation between society and forests in Bolivia, Cameroon and Indonesia.